Analyzing Transparent and Accountable Financial Management in West Bandung Regency - Kurniawan, Asep; Solikin, Ikin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Transparent and accountable governance requires effective internal control and quality financial information systems. The purpose of this study is to examine the effectiveness of internal control in West Bandung Regency, determine the quality of accounting information in the West Bandung Regency Local Government, and assess the level of effectiveness of accounting implementation in transparent and accountable governance in the West Bandung Regency Government. The research method used by the author generally employs a descriptive-analytical approach, which involves discussing, interpreting, and writing about the research object through data collection and processing activities, followed by data analysis and the drawing of general conclusions from the issues discussed. The research results indicate that the internal control system in the West Bandung Regency Government is categorised as good in terms of the control environment, risk analysis, and control activities conducted in 2020. The quality of financial information and communication in Bandung Barat Regency is relatively good in terms of communication and information indicators, as well as monitoring of current and expected cases. The implementation of financial management in Bandung Barat Regency is categorised as very good, as seen from the indicators of current and expected financial management conditions.